Interactions between animal temperament and exposure to endophytic tall fescue: Effects on cell-mediated and humoral immunity in beef heifers - Altman, A.W.; Adams, A. A.; McLeod, K. R.; Vanzant, E. S. (Frontiers in Animal Science, 2023)
Two experiments (n=12 Angus heifers/experiment) investigated influences of animal temperament, as indicated by exit velocity (EV; determined at weaning) and consumption of toxic endophyte-infected tall fescue seed on peripheral lymphocyte production of interferon-γ. Heifers were selected from calves born on the University of Kentucky’s C. Oran Little Research Center. In experiment 1, calves were randomly selected from 50 heifers within a single calf crop. In experiment 2, calves with the 6 fastest and 6 slowest EV in the subsequent year’s calf crop were selected. In both experiments, heifers were assigned to either high or low EV treatments based on relative ranking, and endophyte treatments (toxic endophyte-infected, E+, or endophyte-free, E-, fescue seed) were balanced by body weight. Rations were restricted to 1.8x NEm and common diet was top-dressed with fescue seed each morning. Experiment 1 had four phases (pre-endophyte treatment/thermoneutral, increased room temperature, increased room temperature/endophyte treatment, and post-endophyte/thermoneutral) and experiment 2 had two phases (increased room temperature/endophyte treatment and thermoneutral). During endophyte treatment phases, heifers were fed their respective treatment seed. During all other phases, all heifers received E- seed. In experiment 1, proportions of lymphocytes producing interferon-γ were decreased in E+ heifers during the heat/endophyte phase (P=0.03) whereas during the subsequent thermoneutral period this response was greater in high, compared with low, EV heifers on E- treatment, with no difference observed among E+ heifers (interaction P=0.08). Also during the recovery phase, average lymphocyte production of interferon-γ was higher in E+ heifers (P=0.01). Consistent with experiment 1 findings, during the recovery period of experiment 2, endophyte exposure increased the per cell production of interferon-γ (P<0.01). In this experiment, the difference was of sufficient magnitude to result in a concomitant increase (P=0.03) in total interferon-γ production during that period. These results indicate peripheral lymphocyte production of interferon-γ can be influenced by both EV and endophyte exposure following periods of increased ambient temperature humidity indices, though there was minimal indication of interactions between temperament and alkaloid exposure. This may imply that cattle with high exit velocities and those previously exposed to toxic endophyte-infected tall fescue are better poised against cell-mediated challenges.